Odpowiedzi

2010-03-03T21:18:57+01:00
A) ⅔ (x-2) -1≤ x+1
2/3x-4/3-1-x-1≤0
-1/3x-10/3≤0
-1/3x≤10/3
x≥-10
b) 3(x+2) -5≥4x-1
3x+6-5-4x+1≥0
-x≥-2
x≤2
c)2x- (1-x) < 2 (x+3)+x-1
2x-1+x<2x+6+x-1
3x-1<3x+5
3x-3x<5+1
zero
d) (2x-3)(x+2)+1≤2[(x+3)(x-2)-1]
(2x²+4x-3x-6)+1≤2*[x²-2x+3x-6-1]
2x²+x-5≤2x²+2x-14
2x²+x-5-2x²-2x+14≤0
-x≤-9
x≥9
e) 2(x+6)(x-2)>3(x-1)+1+2x(x-1,5)
2(x²-2x+6x-12)>3x-3+1+2x²-3
2x²+8x-24>3x+2x²-5
2x²+8x-24-3x-2x²+5>0
5x>19
x>19/5
2010-03-03T21:20:49+01:00
A. ⅔ (x-2) -1≤ x+1
2/3x - 4/3x - 1 _< x+1 |*3
3*2/3x - 3*4/3 - 3 _< 3x + 3
2x - 4 - 3 _< 3x + 3
2x - 3x _< 3 + 3 + 4
-1x _< 10 | : (-1)
x >_ -10

B. 3(x+2) -5≥4x-1
3x + 6 -5 >_ 4x - 1
3x - 4x >_ -1 +5 - 6
-1x >_ -2|: (-1)
x _< 2

C.2x- (1-x) < 2 (x+3)+x-1
2x - 1 + x < 2x + 6 + x - 1
2x + x - 2x - x < -1+6+1
0x < 6 |: 0
x < 0

D. (2x-3)(x+2)+1≤2[(x+3)(x-2)-1]
2x do potęgi drugiej + 4x - 3x - 6 + 1 _< 2( x do potegi drugiej - 2x + 3x -6 - 1
2x^ + 4x - 3x - 6 + 1 _< 2x^ - 4x + 6x -12 -2
2x^ + 4x - 3x - 2x^ + 4x - 6x _< -2-12-1+6
-3x _< -9 |: (-3)
x >_ 3